Online Ruqyah in The Digital Age: A Tawhid Based Critical Analysis from Al-Qur’an and Hadits - Nur Fathin Hakim; Maritsa Zein; Agung Pranoto Kadiatmaja (Al-Hukumah: Jurnal Ilmu Pemerintahan dan Studi Islam, 2026)
This study critically examines the phenomenon of online Ruqyah in the digital era through a Tawhid based theological framework derived from the Qur’an, Hadith, and classical works such as Kitab At-Tauhid by Muhammad ibn Abd al-Wahhab. It explores whether this digital adaptation of spiritual healing aligns with the principles of Ruqyah Shar‘iyyah and safeguards the purity of Tawhid al-Uluhiyyah. Employing a qualitative library research approach, the study analyzes Qur’anic texts, Prophetic traditions, and scholarly literature on digital Islam. Findings indicate that while online Ruqyah enhances accessibility and serves as a medium for da’wah and spiritual education, it fails to fulfill the essential methodological (kayfiyyah) elements prescribed in the Sunnah particularly Masah (wiping) and Nafth (blowing) thereby challenging its theological validity as affirmed by scholars such as Shaykh Al-Fawzan. The digital mediation of supplication, absent during the Prophet’s era, further risks bid‘ah (religious innovation) and dilutes the sincerity (ikhlāṣ) and tawakkul central to authentic worship. Nevertheless, the study underscores the need for empirical engagement with users’ experiences to evaluate whether digital Ruqyah may function as a complementary form of guided self Ruqyah and an evolving expression of faith within contemporary digital religiosity.